Myricitrin regulates proliferation, apoptosis and inflammation of chondrocytes treated with IL-1Î² - Sun, Tao; Xue, Jian-Bo; Zhou, Ying-Ling; Wang, Xiao-Feng (Cellular and Molecular Biology, 2020)
Osteoarthritis (OA) is a clinical disease which seriously affects the quality of life of sufferers. Although the pathogenesis of OA has not been fully unraveled, it is may be due to increased levels of pro-inflammatory cytokines, activation of inflammation-related signaling pathways, and degradation of extracellular matrix. Osteoarthritis is characterized by chronic joint pain, swelling, stiffness, limited movement or joint deformity, all of which seriously affect the quality of life and health of the affected individuals. Myroside (Myr) is a polyphenolic hydroxyflavone glycoside extracted from the fruits, bark and leaves of myroside and other natural plants. It has many pharmacological properties, especially anti-inflammatory effects. In the present study, primary chondrocytes of IL-1Î² rats were used to simulate pathological environment of chondrocytes in OA, and to explore the effect of Myr on chondrocytes. It was found that Myr improved the viability and proliferation of chondrocytes, and also inhibited apoptosis in these cells. Moreover, Myr reduced the expressions of inflammatory factors, and inhibited inflammatory reactions in chondrocytes. These findings provide good experimental basis for the clinical application of Myr in the prevention and treatment of progressive degeneration of cartilage in OA.